SVD based reconfigurable SRC filter for multi-standard radio receivers - Agarwal, Ashok; Bopanna, Lakshmi (IET circuits, devices & systems, 2016)
With the recent growth in wireless industry, and changes that occur at a faster pace in radio standards, software defined radio (SDR) provides a flexible solution when compared with hardware radios. Channelisation and sample rate conversion (SRC) are two computational intensive tasks to be carried out in SDR receivers. Reconfigurable anti-aliasing filter and channeliser with minimum reconfiguration overhead is needed for the design of SDR receivers. Low complexity, coefficientless cascaded-integrator-comb filters provides flexible reconfiguration for SRC over a wide integer range, but offers gain droop in the passband of interest. Moreover, they are not suitable for achieving SRC by fractional rates. In this study, the authors propose the design of variable digital filter (VDF) for gain droop compensation and fractional SRC to meet the spectral characteristics of multiple radio communication standards, employing singular value decomposition algorithm. The proposed design of VDF is tested for its reconfigurability with four radio standards, namely, GSM900, WCDMA/CDMA 2000 and WiMAX 802.16. Simulations carried out in MATLAB showed that the proposed VDF had improved spectral response in comparison to other methods proposed in literature.